Long-term phosphorus fertilization reveals the phosphorus limitation shaping the soil micro-food web stability in the Loess Plateau - Li, Liangliang; Luo, Zhuzhu; Li, Lingling; Niu, Yining; Zhang, Yaoquan; He, Renyuan; Liu, Jiahe; Nian, Lili (Frontiers in Microbiology, 2024)
The intricate decomposition pathways within soil micro-food webs are vital for cycling soil organic carbon and nutrients, influencing the quality, productivity, and sustainability of soil systems. Yet, the impact of diverse phosphorus additions on these organic decomposition pathways still needs to be explored. In an 8-year experiment, phosphorus (P) fertilizer was added at varying levels (0 kg ha -1 , CK; 60 kg ha -1 , P60; 120 kg ha -1 , P120; 180 kg ha -1 , P180) to investigate the response of the soil micro-food web. Results revealed a significant effect of P addition on soil microorganisms and nematodes, with P60 exerting a greater influence than other treatments. At P60, the Shannon index of nematodes and fungi surpassed other treatments, indicating higher diversity, while the Shannon index of bacteria was lower. The Chao1 index of bacteria and fungi at P60 was higher, contrasting with the lower index for nematodes. Bacterivore' and omnivores-predators' metabolic footprints (BFMF and OPMF) were higher at P60, while fungivores' and plant parasites' metabolic footprints (FFMF and PPMF) were lower, signifying altered energy flow. Functional metabolic footprints and energy flow analysis unveiled a stable soil micro-food web structure at P60, with enhanced energy conversion efficiency. Network analysis illustrated positive correlations between fungi, fungivorous nematodes (FF), and omnivorous-predatory nematodes (OP) at P60, while P120 and P180 showed positive correlations among bacteria, bacterivorous nematodes (BF), and OP. Path analysis underscored the higher contribution rate of BF-C, FF-C, and OP-C to soil organic carbon at P60 compared to P120 and P180. These findings suggest that nutrient interactions between fungi and nematodes regulate soil micro-food web decomposition under low P concentrations. In contrast, interactions between bacteria and nematodes dominate at high P concentrations. The study indicates that adding P has nuanced bottom-up effects, intricately shaping the structure and activity of pathways, underscoring the need for a comprehensive understanding of nutrient dynamics in soil ecosystems.